الدراسة الطيفية للمركب: (1-x) -(x) BaTiO3 (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
لقد تم تحضير المركب (1-x) Co0.6 Zn0.4 Fe2 O4 + (x) BaTiO3 (x=0, 0.25 , 0.75 ,1) المكوّن من طور فرايت( كوبالت – زنك)، وطور تيتنات الباريوم ذات الخواص الفروكهربية بالطريقة السيراميكية المألوفة. وتم إيجاد بارامترات الشبكة البلورية لطور الفرايت، وطور تيتنات الباريوم للعينات المدروسة من طيوف انعراج أشعة -   Xبينما استخلصت مواقع عصابات الامتصاص وشدتها في كلا الموقعين الرباعي A والثماني B للفرايت من طيوف الأشعة تحت الحمراء. ولاحظنا أن النسبة c/a تقترب من قيمتها في الطور المكعبي، وذلك بزيادة محتوى الفرايت في العينات المدروسة. System of composites (1-x) Co0.6 Zn0.4 Fe2 O4 + (x) BaTiO3 (x=0, 0.25 , 0.75 ,1) was prepared by general ceramic method. The lattice parameters in ferrite phase and barium titanate phase for the understudied samples were found from the diffraction pattern, while the positions of the absorption band and their relative corresponding intensity in both tetrahedral A and octahedral B sites were inferred from IR spectra. We noticed that the tetragonality ratio c/a approximates its value in the cubic phase with increasing ferrite contents.